L'environnement des églises et la topographie religieuse des campagnes médiévales - Fixot, Michel; Zadora-Rio, Elisabeth (Documents d'archéologie française, 1994)
This volume comprises the published proceedings of a conference organized by the Société d'archéologie médiévale and the Groupement de recherche 94 of the CNRS which was held at Aix-en-Provence between September 1989 28th and 30th. The papers were grouped according to three themes which play a leading part in the study of medieval rural settlement. The first deals with the influence of late Antiquity on the religious topography of the medieval countryside and the problem of continuity of the ecclesiastical and funerary use of sites. The second adresses the role of churches as foci for the organisation of settlement; this phenomenon, which was promoted by the interests of the Peace of God movement, formed the basis of units of population which appear sometimes to have been in competition with the emergent system of castellanies. The last theme concerns the organisation of ecclesiastical estates.